(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Acute kidney injury (AKI) is a frequent and clinically significant complication in critically ill pediatric patients, associated with increased morbidity, prolonged intensive-care stay, and adverse outcomes. Despite its high incidence, early identification remains challenging owing to the inherent limitations of conventional diagnostic markers. Objectives:To determine the incidence of AKI and its severity among sick children admitted to a tertiary care Pediatric Intensive Care Unit (PICU). Methods: This prospective observational study was conducted over 18 months at Government Children’s Hospital, Bemina, Srinagar. Seventy-five children aged 1 month to 18 years admitted to the PICU for a minimum of 48 hours were enrolled. Serum creatinine, urine output, and fluid balance were assessed at baseline, 12 hours , Day3, and Day7. AKI was classified using Kidney Disease: Improving Global Outcomes (KDIGO) criteria. Results: Severe AKI was observed in 42.67% of the study population, with 37.33% and 26.67% of patients meeting criteria on Day 3 and Day 7 respectively. Serum creatinine rose progressively from a mean baseline of 0.49 ± 0.14 mg/dL to 1.37 ± 1.34 mg/dL by Day 3. Renal replacement therapy (RRT) was required in 24.00% of patients. Overall mortality at 28 days was 33.33%. Patients with severe AKI exhibited significantly higher creatinine levels, lower urine output, and greater clinical injury scores (all p < 0.001). Conclusions: More than 40% of critically ill pediatric patients are affected by AKI, and is associated with significant disease severity and mortality.